Influence of first language on English word stress assignment by bahdini Kurdish learners of English - Mohammad , Mazheen; Hasan, Aveen (Humanities Journal of University of Zakho, 2023)
Studies on learning second language (L2) phonology agree that first language (L1) has a key role in the production of learners L2. This study was carried out on Bahdini Kurdish (henceforth, BK) learners of English in order to investigate how phonological characteristics of Kurdish word stress affect the production of English word stress as far as the two languages have different stress placement rules. It was hypothesized that BK learners will face challenges in learning English stress and they will, more frequently, place stress on the final syllable of the English words, similar to their L1. Thirty students from the English Language Department at University of Zakho participated in this study. The participants completed a production test of reading 48 English words with different grammatical categories, stress positions and morphological structures. The learners’ production was recorded and listened to by the researcher and two phonologists to indicate the correct stress placement in their performance. The results show that BK learners were not able to place stress on the correct syllable of all types of words in English: simple, complex and compound. Furthermore, language transfer was not clear in the learners’ performance of the test words, that is, they did not place stress on the final syllable of the words. The learners were unaware of English stress rules and English pronunciation in general and did not properly acquire them. Mispronunciation of words and parts of the words and lack of knowledge about English stress rules, therefore, were clearly the factor of stress misplacement in all types of words.